Case report: Hashimoto’s thyroiditis after CD19 chimeric antigen receptor T-cell therapy - Chen, Panpan; Xia, Yongming; Lei, Wen; Zhong, Shuhan; Jiang, Huawei; Ren, Lingling; Qian, Wenbin; Liu, Hui (Frontiers in Immunology, 2022)
Chimeric antigen receptor (CAR) T cell therapy is a novel cell therapeutic approach that is increasingly being used to treat patients with relapsed refractory B-cell lymphoma. Despite the efficacy of CAR T cell therapy, it has various adverse effects that can affect any organ in the body. The application of immune checkpoint inhibitors such as programmed death 1 (PD-1), programmed death ligand 1 (PDL-1), and cytotoxic T-lymphocyte antigen 4 (CTLA-4) antibodies has previously been reported to be associated with immune-related adverse events such as thyroid dysfunction and thyroiditis. Reports of immune-related adverse reactions after CAR T therapy are currently extremely rare, with only one case of a cytokine storm (CRS) combined with severe arthritis in a patient with ALL after treatment. Here, we describe two cases of Hashimoto's thyroiditis secondary to CAR T therapy. Two patients with relapsed refractory diffuse large B-cell lymphoma developed elevated peroxidase and globulin antibodies secondary to CAR T cell therapy and developed Hashimoto's thyroiditis. Complete remission was achieved in two patients at 1 and 3 months after CAR T cell therapy. The inflammation of the thyroid tissue may be directly or indirectly related to CAR T cell therapy, and the mechanisms needs to be further investigated.